1993
DOI: 10.1111/j.1365-2559.1993.tb01178.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactive human bile ductules express parathyroid hormone‐related peptide

Abstract: Various cholestatic liver diseases as well as regeneration after submassive necrosis are accompanied by a striking increase in the number of bile ductules. These reactive bile ductules are thought to arise either from proliferation of pre-existing bile ductules or bile ductule-related facultative stem cells, or from ductular metaplasia of hepatocytes. Recently, we found that reactive bile ductules display neuro-endocrine features, and speculated that the substance(s), produced in the neuro-endocrine granules, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…148 It is hypothesized that bile acids may stimulate growth of primitive liver ''stem'' cells, while also promoting differentiation of more mature liver and bile duct cells. 149 The detection of neuroendocrine markers, such as parathyroid hormonerelated peptide, 47,150 in biliary cells indicates that reactive bile ductular cells may have an autocrine or paracrine effect in the control of liver cell proliferation and differentiation, 47 perhaps controlling the expression of the biliary phenotype. 150 Atypical ductular cells may also contribute factors, such as TGF-␤, that lead to transformation of perisinusoidal Ito cells into myofibroblasts [151][152][153] and the eventual development of fibrosis leading to cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…148 It is hypothesized that bile acids may stimulate growth of primitive liver ''stem'' cells, while also promoting differentiation of more mature liver and bile duct cells. 149 The detection of neuroendocrine markers, such as parathyroid hormonerelated peptide, 47,150 in biliary cells indicates that reactive bile ductular cells may have an autocrine or paracrine effect in the control of liver cell proliferation and differentiation, 47 perhaps controlling the expression of the biliary phenotype. 150 Atypical ductular cells may also contribute factors, such as TGF-␤, that lead to transformation of perisinusoidal Ito cells into myofibroblasts [151][152][153] and the eventual development of fibrosis leading to cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…149 The detection of neuroendocrine markers, such as parathyroid hormonerelated peptide, 47,150 in biliary cells indicates that reactive bile ductular cells may have an autocrine or paracrine effect in the control of liver cell proliferation and differentiation, 47 perhaps controlling the expression of the biliary phenotype. 150 Atypical ductular cells may also contribute factors, such as TGF-␤, that lead to transformation of perisinusoidal Ito cells into myofibroblasts [151][152][153] and the eventual development of fibrosis leading to cirrhosis. 21 During fetal development in animals [154][155][156][157][158][159][160][161][162] and humans, 7,163-167 bile ducts and hepatocytes both originate from a common ''bipolar'' hepatoblast.…”
Section: Discussionmentioning
confidence: 99%
“…In man, PTHrP is expressed in reactive bile ductules of cholestatic and regenerating liver (Roskams et al 1993a), as well as by cholangiocarcinomas (Roskams et al 1993b). As growth factors such as EGF can rapidly induce PTHrP synthesis in cultured ductular cells, PTHrP could be a member of the early response gene family, and the peptide may have an autocrine role in bile ductular reactions (Roskams et al 1995).…”
Section: Growth Factors Controlling Oval Cell Behaviourmentioning
confidence: 99%
“…95,96 The early, transient expression of the extracellular matrix component tenascin showed that ductular reaction represents a pacemaker for progressive fibrosis in chronic cholestasis, analogous to the fibrosis-inducing role of interface hepatitis in chronic inflammation. 97,98 The study by Dr. Vanstapel and colleagues on S100 protein in ductules, 99 and the results by Dr. Roskams and colleagues on ductular expression of neuroendocrine markers 100,101 (Fig. 8) focused more on type III ductular reaction, emphasizing the existence in human liver of progenitor cells [100][101][102] with a multidrugresistant phenotype, which is of high importance in regeneration and carcinogenesis.…”
Section: Cholestasismentioning
confidence: 99%
“…97,98 The study by Dr. Vanstapel and colleagues on S100 protein in ductules, 99 and the results by Dr. Roskams and colleagues on ductular expression of neuroendocrine markers 100,101 (Fig. 8) focused more on type III ductular reaction, emphasizing the existence in human liver of progenitor cells [100][101][102] with a multidrugresistant phenotype, which is of high importance in regeneration and carcinogenesis. 103,104 Further investigations by Dr. Roskams's team revealed expression of neuroendocrine markers in coproliferating hepatic stellate cells as well, leading to the concept of a neuroendocrine compartment in the liver and its neuroregulation.…”
Section: Cholestasismentioning
confidence: 99%